Identification of Novel Biomarkers in Pancreatic Tumor Tissue to Predict Response to Neoadjuvant Chemotherapy - Sahni, Sumit; Nahm, Christopher; Krisp, Christoph; Molloy, Mark P.; Mehta, Shreya; Maloney, Sarah; Itchins, Malinda; Pavlakis, Nick; Clarke, Stephen; Chan, David; Gill, Anthony J.; Howell, Viive M.; et al. (Frontiers in Oncology, 2020)
Background: Neoadjuvant chemotherapy (NAC) has been of recent interest as an alternative to upfront surgery followed by adjuvant chemotherapy in patients with pancreatic ductal adenocarcinoma (PDAC). However, a subset of patients does not respond to NAC and may have been better managed by upfront surgery. Hence, there is an unmet need for accurate biomarkers for predicting NAC response in PDAC. We aimed to identify upregulated proteins in tumor tissue from poor- and good-NAC responders. Methods: Tumor and adjacent pancreas tissue samples were obtained following surgical resection from NAC-treated PDAC patients. SWATH-MS proteomic analysis was performed to identify and quantify proteins in tissue samples. Statistical analysis was performed to identify biomarkers for NAC response. Pathway analysis was preformed to characterize affected canonical pathways in good- and poor-NAC responders. Results: A total of 3156 proteins were identified, with 19 being were significantly upregulated in poor-responders compared to good-responders (log2ratio >2, p<0.05). Those with the greatest ability to predict poor-NAC response were GRP78, CADM1, PGES2 and RUXF. Notably, canonical pathways that were significantly upregulated in good-responders included acute phase signalling and macrophage activation, indicating a heightened immune response in these patients. Conclusion: A novel biomarker signature for poor-NAC response in PDAC was identified.